PENGARUH KONDISI LABORATORIUM TERHADAP KETERAMPILAN PROSES SAINS SISWA SMA NEGERI 11 SEMARANG (DESKRIPTIF KUALITATIF) - Afifah, Kunnti; Astuti, Andari Puji (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The laboratory is a place to conduct practicum activities, research, new technologies that support the learning and teaching process for services to the community. The science-learning process emphasizes the provision of hands-on experience to develop competencies to explore and understand the natural surroundings scientifically. Science as a scientific process means that acquiring knowledge of the universe requires a process to be lived. This study aims to determine the effect of laboratory conditions on the science process skills of SMA Negeri 11 Semarang students. This research was conducted at state high school 11 Semarang by using approach of skin research. Technique of data collecting by using data triangulation method that is observation, interview and questionnaire (questionnaire). The subjects of this study are laboratory managers, teachers, and students of class XII MIPA 5 and XII MIPA 6 SMA Negeri 11 Semarang academic year 2016/2017. Data taken from this research are 1) Standardization of chemical laboratory and 2) Activities in Laboratory Keywords :  Laboratorium, Keterampilan Proses Sains Siswa